Project-Based Learning Design for Internalization of Environmental Literacy with Islamic Values - Farida, I.; Hadiansyah, H.; Mahmud, M.; Munandar, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This research aims to produce teaching and learning design to develop environmental literacy among students through project-based learning to internalize the Islamic values. The program was developed through research and development design with three phases: a preliminary study, development program, and feasibility studies. This research produces three characteristics of the teaching and learning programs i.e.: (a) Developing environmental literacy of students based on Islamic values by using project-based teaching and learning; b) Developing the main themes of ‘Green Living’ of which is divided into four sub-themes: ‘Save our water,’ ‘Save our Soil,’ ‘Use Eco-friendly Products’ and ‘Waste for Life’; c) Facilitating students to conduct learning activities, in order to develop scientific skills and environmental literacy. The design model was validated by experts’ judgment. The tests showed that this design is feasible to be used in courses. It is suggested that the theme be broadened to include other relevant themes with environmental issues. The study is recommended to be followed up with testing and implementation by integrating the themes in other relevant subjects.